Segmentation of Written Words in French. (March 2013) - Chetail, Fabienne; Content, Alain
Syllabification of spoken words has been largely used to define syllabic properties of written words, such as the number of syllables or syllabic boundaries. By contrast, some authors proposed that the functional structure of written words stems from visuo-orthographic features rather than from the transposition of phonological structure into the written modality. Thus, the first aim of the study was to assess whether the explicit segmentation of written words in French was consistent with syllabification patterns for spoken words previously reported. Second, given that spelling does not map perfectly with phonology, we examined how readers segmented printed words with grapheme/phoneme misalignments. The examination of the whole patterns of written segmentation produced by participants showed that, though written segmentation followed spoken segmentation for words matched for phonological/orthographic forms, discrepancies were found in cases of mismatch, therefore suggesting that readers rely on orthographic cues to parse printed strings of letters. This conclusion was confirmed with an on-line letter detection task.